EFEKTIVITAS PENDAFTARAN CIPTAAN TERHADAP KARYA CIPTA SENI PATUNG DI DESA JAGAPATI KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Heri Hendrawan, Putu; Wirta Griadhi, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013, 2013)
Copyright protection has arises automatically, although copyright protection arises automatically in order to prevent copyright infringement will recognize the registration of creation. The problem is how the effectiveness of the registration of the creation of creative works of art sculpture in the village jagapati. This writing method using an empirical method with empirical juridical approach. This study concluded that the ineffectiveness of the registration in the village jagapati caused due to the high cost of the registration.
Keywords: Effectiveness, Registration Creation, Copy Right